Pemetaan Kebutuhan Pengembangan Bahan Ajar Digital - Ismail Saleh Nasution; Eko Febri Syahputera Siregar; Achmad Yuhdi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study intends to map the needs of the PGSD FKIP UMSU academic community on the development of digital teaching materials that can be accessed by students at any time because they are integrated with Android. This research is part of the research development (R&D). This type of research is an expo facto research where the researcher collects data directly from the respondent through a data collection instrument. The data collection process is a very important stage in research. The data to be collected will later be used to test the hypotheses proposed in the study where the data is obtained through interviews, questionnaires, and observations. The data analysis technique was done by using quantitative descriptive method. The results showed that there was a positive trend towards the need for digital-based teaching materials development in PGSD FKIP UMSU Study Program. So far, there has not been a single teaching material packaged by lecturers in digital form in the study program. The results of a questionnaire to students showed that 90% of students needed teaching materials that could be accessed by them at any time and wherever they were.